Pengaruh Profitabilitas, Likuiditas, dan Beban Dibayar Dimuka terhadap Durasi Audit pada Perusahaan Consumer Goods Periode 2022-2024 - Rhiesma Cantika Tyas Findriana Meilani; Syahira Najla; Nazwa Aulia Triyani; Kamilah Rohadatul Aisy Mustofa; Ricky Bryan D.P. Tampubolon (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2026)
This study aims to examine the effect of profitability, liquidity, and prepaid expenses on audit duration in consumer goods companies during the 2022–2024 period. The research adopts a quantitative approach, using a total of 38 observations obtained from published financial statements. Descriptive statistics, classical assumption tests, and multiple linear regression analysis are employed to assess the influence of independent variables on audit duration as the dependent variable. The findings indicate that profitability, liquidity, and prepaid expenses do not have a significant impact on audit duration, both partially and simultaneously. These results suggest that the financial factors examined in this study are not the primary determinants of audit timing, and other factors such as transaction complexity, auditor workload, and public accounting firm policies may play a more substantial role. This study provides insights for companies and auditors to better understand factors affecting audit efficiency and highlights the need for future research to incorporate additional variables and more comprehensive analytical methods to explain variations in audit duration.